Pengaruh Busi Racing, Groundstrap pada Kabel Koil dengan Remap ECU terhadap Performa Honda Beat FI - Dwiyanto, Indra Bagaskara; Budiman, Febrian Arif; Hadromi, Hadromi; Gojandra, Farda Pega Libra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The use of Honda Beat motorcycles in 2016 is still quite dominant among two-wheeled vehicle users. One of the efforts to improve vehicle performance is done by replacing standard spark plugs with racing spark plugs, installing groundstraps on coil cables, and modifying the ECU remap using the Juken 5 ECU with a limiter increased to 10,000 RPM. Groundstraps play a role in stabilizing the flow of electric current in the vehicle's electrical system, so that it can increase ignition efficiency and produce stronger and more consistent sparks on the spark plugs. The purpose of this study was to determine the effect on the performance of Honda Beat FI motorcycles that use racing spark plugs, groundstraps on coil cables and ECU remaps. This study needs to be done, so that motorcycle users can improve vehicle performance by adding groundstraps to the high-voltage coil cables. This study uses an experimental method. Dynotest is used to determine the resulting performance. The first step taken, testing, tuning and continued testing. The results showed that standard conditions produce a torque of 6.97 N.m and a power of 6.3 HP; The condition without a groundstrap produces 6.98 N.m of torque and 6.9 HP of power; while the condition with a groundstrap produces 6.99 N.m of torque and 6.4 HP of power. The torque generated by testing using a groundstrap increased compared to standard conditions, and power output also increased. Therefore, the use of a groundstrap and ECU remap affects the motorcycle's torque and power performance. Torque is essential for acceleration and climbing, while power influences top speed.